Identifying brain functional alterations in postmenopausal women with cognitive impairment. Issue 3 (July 2015) - Huang, Jingjing; Bai, Feng; Yang, Xiaoqing; Chen, Chen; Bao, Xueping; Zhang, Yuquan
Highlights Multi-dimension of cognitive dysfunction was observed in postmenopausal women. Disrupted subcortical–cortical loops were in postmenopausal women with MCI. Left precuneus was associated with altered episodic memory in postmenopausal women.